The analysis of errors in the use of articles by the Bengali learners of English (IIUC Studies, 2026)
The present study investigates the kinds of errors committed by the secondary school students of class ten of Hashimpur M.A.K.U High School in Chattogram of Bangladesh. The main goal of the study is to improve the knowledge of using articles correctly through analyzing the errors. Data were gathered from the written essays of 52 students (boys and girls) and the test to fill in the blanks they were asked to fill with appropriate articles. Seven types of errors were identified and counted in frequency. They are-1. errors of substitution of an for a, 2. errors of substitution of a for an, 3. errors of omission of the definite article, 4. errors of using indefinite article with unmarked plurals, 5. errors of using indefinite article with adjectives, 6. errors of using definite article with non-count nouns, and 7. errors of using indefinite article with non-count nouns. The study revealed that most of the errors committed by the students were rooted in strategies like simplification, overgeneralization, or a few that could be traced back to the influence of the native language, Bangla. The findings can potentially bring necessary changes in teaching strategies and materials.IIUC Studies, Vol.-21, Issue-1, Dec. 2024, pp. 105-116